“KULWAP: MEDIA EDUKASI DI MASA PANDEMI COVID-19” - Ivanna Beru Brahmana (Universitas Jenderal Soedirman, 2021)
ABSTRACT. Background: The spreading of the Covid-19 virus has an impact on social interactions that not going normally. It is difficult to carry out community service activities in the field based on many participants, must stay at home and social distancing. Reproductive health education is important to be disseminated on an ongoing basis. Whatsapp is the most frequent application that people use intensity. One of the educational methods in the whatsapp application called lecturing via whatsapp (kulwap) could be an alternative for implementing community service during pandemic. Purpose: To use whatsapp optimally as a means of education during pandemic. Methods: lectures using powerpoint and voice notes, discussion and Q&A (question and answer) with chat and voice notes, and filling out questionnaires using google form. Results and implications: 100% (51/51) of participants received benefits additional knowledge and friendship. 100% (51/51) of the participants say the material is conveyed well and the discussion is smooth. The results of community service are published manuscript in the national service journal. Conclusion: Kulwap is an affordable and simple social media so that the discussion remains enthusiastic, and the material can be conveyed well. Kulwap is also an alternative for community service during this pandemic.Keywords: kulwap, education, pandemic.ABSTRAK. Latar belakang: Pandemi Covid-19 terjadi secara tidak terduga. Tatanan kehidupan bersosialisasi tidak lagi bisa dilakukan secara normal. Pengabdian masayarakat yang identik dengan kegiatan berkelompok, dihadiri banyak peserta, sulit dilakukan. Stay at home, social distancing, merupakan pagar upaya pencegahan yang harus ditaati. Edukasi kesehatan reproduksi masih perlu ditingkatkan dan disosialisasikan secara berkesinambungan. Melek teknologi menjadi suatu keharusan. Sosial media whatsapp (wa) digunakan oleh hampir setiap orang, karena kebutuhan handphone sudah tidak bisa disangkal lagi. Kulwap, kuliah via whatsapp, menjembatani pelaksanaan pengabdian masyarakat tetap berlangsung di masa pandemi, penyuluhan tersalurkan, walau ada keterbatasan. Tujuan: memaksimalkan wa sebagai sarana edukasi di masa pandemi. Metode: ceramah menggunakan powerpoint dan voice note, diskusi dan tanya jawab dengan chatting dan voice note, dan pengisian kuesioner dengan google form. Hasil dan implikasi: 100% (51/51) peserta pengabdian merasakan manfaat yang lebih dari wa dengan adanya tambahan ilmu, silaturahmi tetap terjaga, sederhana karena terbiasa menggunakan wa, dan 100% (51/51) peserta merasa nyaman dan materi tersampaikan dengan baik, dan diskusi berjalan lancar. Luaran pengabdian berupa naskah publikasi di jurnal pengabdian nasional. Kesimpulan: Kulwap merupakan sosial media yang murah, meriah, sederhana, diskusi tetap antusias, dan materi tersampaikan, suatu sarana pengabdian masyarakat di masa pandemi ini.Kata kunci: kulwap, edukasi, pandemi.